Does Foreign Ownership from China and Hong Kong Decrease Investment Efficiency of Malaysia Firms? An Empirical Investigation - Hii, Joseph Wee Siong; Subramaniam, Thirunaukarasu (INTERNATIONAL JOURNAL OF CHINA STUDIES, 2025)
Foreign investment is becoming increasingly significant in emerging economies, but its effect on efficiency of domestic firms remains ambiguous. In Malaysia, foreign ownership is subject to regulatory restrictions and institutional frameworks. It remains unclear, however, whether foreign investors contribute to efficient capital allocation. Therefore, this study conducted an in-depth analysis on 455 public listed Malaysian firms, specifically on the relationship between foreign ownership and firm-level capital allocations, captured by sensitivity of investment expenditure to investment opportunities (investment-Q sensitivity). The findings indicate that foreign ownership has no significant impact on investment efficiency, and this is consistent across different ownership intervals. Nevertheless, the effect of foreign ownership varies by country of origin. Investments from Japan, Singapore and Western countries have had no significant impact on investment efficiency, while those from China and Hong Kong are associated with significant reduction. The findings, hence, suggest the importance of investor origin and fit when formulating investment policies and designing governance frameworks to facilitate efficient capital allocation.